Ethno-Aesthetic Communication in the Context of the Formation of Technological Culture of Students in the System of Continuing Education - Galeeva, Alsou I. (2021)
The relevance of the problem presented in this study is conditioned by the fact that the multifactorial nature of qualities of technological culture of the individual requires a search for paradigms, an identification of the range of approaches aimed at developing not only technological, professional, but also cultural competences of students in multiparadigmatic viewpoint. The purpose of the article is to theoretically substantiate the polyparadigmatic approach to the formation of technological culture of students in the system of continuing education based on ethno-aesthetic values. The leading method for the research of this problem is the method of concretization, which allows us to consider the formation of motivational, cognitive, activity (practical) - technologically important personal qualities (Belentsov S. I, Fahrutdinova A. V, 2017). The structure of the polyparadigmatic approach to the formation of technological culture of students in the system of continuing education based on ethno-aesthetic values includes axiological, cultural, socio-cultural, activity-technological, ethnopedagogical, and ethno-aesthetic approaches. The polyparadigmatic approach has an integrative basis, it is based on scientific and ethnic knowledge expressed in the form of concepts, didactics of technological and higher education, ethno-aesthetic didactics, which ensure the continuity of the formation of the components of technological culture of students in the system ‘school – University – additional education’.